REKONSTRUKSI KEBIJAKAN PENCEGAHAN KEKERASAN SEKSUAL DI PESANTREN: PENDEKATAN MAQĀṢID AL-SYARĪ'AH SEBAGAI BASIS INTEGRASI DENGAN HUKUM PIDANA NASIONAL - Muhammad Hafiduddin; Afif Hasbullah; Ahmad Munir; Ahmad Zeeya Ulya Eldavi; Desi Lusiawati (Yayasan Merassa Indonesia Publikasi, 2026)
Sexual violence in Islamic boarding school (pesantren) environments constitutes a serious issue demanding a comprehensive and equitable legal policy response. This article examines the reconstruction of sexual violence prevention policies in pesantren through the integration of the Maqāṣid al-Syarī'ah framework with the national criminal law system, specifically Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS) and Ministerial Regulation of Religious Affairs No. 73 of 2022 on Prevention and Handling of Sexual Violence in Educational Units under the Ministry of Religious Affairs. This study employs a normative juridical research method with conceptual and comparative approaches. Legal materials were gathered through library research and analyzed using qualitative descriptive analysis. The findings reveal that the concept of Maqāṣid al-Syarī'ah particularly the dimensions of ḥifẓ al-nafs (protection of life), ḥifẓ al-'aql (protection of intellect), ḥifẓ al-nasl (protection of lineage and honor), and ḥifẓ al-māl (protection of property) possesses substantial convergence with the victim protection values embedded in national criminal law. The proposed policy reconstruction encompasses: (1) internalization of Maqāṣid al-Syarī'ah principles within pesantren regulations; (2) strengthening community-based reporting mechanisms; (3) establishment of integrated service units within pesantren; and (4) reform of Islamic legal education curricula with a gender-sensitive perspective. This research affirms that the integration of Islamic legal epistemology with national criminal law is not merely a normative imperative, but a pragmatic necessity in realizing a holistic protection system for santri